What Education Experts Say About Online Learning before the Covid-19 Issue Hits the World of Education - Gunawan Widjaja; Taufik Rahman; Moch. Isra Hajiri; Abdur Rahman; Rif'ah Rif'ah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
Experts believe that the success of education is closely related to the existence of technology that is adopted into the learning process. The reseachers examined many scientific reports highlighting online learning approaches before the Covid-19 issue hit education to prove this belief. The researchers look for evidence of literature studies from international studies that have succeeded in sounding out educational operations by optimizing technology as a face-to-face companion learning method when students study in class. The data retrieval method is carried out with electronic assistance systems on databases of publication journals such as ERIC, Google Books, Taylor & France, and Sagepub. Next, reseachers analyzed the data using a review system that started with coding and in-depth evaluation techniques and concluded data findings that fairly and accurately answered the research questions. Based on the discussion of the data found, researchers report that online learning activities before the pandemic can help students become successful learners both in the classroom and outside of school. This is highly valid because of evidence from previous literature reviews where online learning is juxtaposed with successful blended learning approaches. Online learning helps students get additional self-study content. Because with online learning, students become more practical, enjoyable, personal, controlled, easy, efficient, focused, and measurable. Keywords: Online Learning, Learning Technology, Covid-19 Issues